Approximation of unbounded functions by trigonometric polynomials - AUAD, ALAA A.; KHRAJAN, MOUSA M. (Journal of College of Education, 2021)
The purpose of this paper is present a brief survey of know on estimates the rate for best approximation of unbounded functions by suitable trigonometric polynomials of one variable in weighted space\ L_{p,α}(X). Moreover two theorems (3) and (4) concerning the rate of trigonometric approximation of f^{(k)} with k non-integer in L_{p,α}(X).